PENGARUH SUKU BUNGA DAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) TERHADAP INVESTASI SEKTOR PROPERTI DI KOTA PEKANBARU PERIODE 2002-2013 - Septha Rusvi Megara; Syapsan '; Anthoni Mayes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the analysis of the Interest Rate and The Gross Domestic Regional Product (GDRP) Variable to Investment Property Sector in Pekanbaru. The data used in this study was a time series data from 2002 to 2013 were sourced from Bank Indonesia and Agency of city planning (Badan Perencanaan Kota). This study used quantitative research methods, and analyzed by using multiple linear regression analysis by using SPSS 21 software programfor Windows computers. In this study, the independent variable was Interest Rate (X1) and Gross Domestic Regional Product (GDRP) (X2) while the dependent variable was Investment Property Sector in Pekanbaru (Y). This study tested thehypothesis of regression coefficient (coefficient of determination, a significant test concurrent / F test, and the significant individual test / t test). The result showed the variable Interest Rate and Gross Domestic Regional Product (GDRP) at once / simultaneously had a significant influence on the Investment Property Sector in Pekanbaru. The individual test / partial showed that Gross Domestic Regional Product (GDRP) variable acquired that contributes greater than the variable Interest Rate to the Investment Property Sector in PekanbaruKeywords:Interest Rate, Gross Domestic Regional Product (GDRP) and Investment Property Sector in Pekanbaru